The dB and gK Stars Near the Direction of the Galactic Center - B. Hidajat; I. Radiman (Institute for Research and Community Services (LPPM) ITB, 1973)
Abstract. An objective prism survey of the Palomar-Groningen Variable-Stars Field no. 3 has been undertaken in order to determine the stellar space distribution of dB and gK stars. A concentration of dB stars has been found at the distances between 150 to 250 pcs. The color excess in this direction is found to remain very low. It only reaches 0m12 at r = 0.5 kpc and remains constant thereafter. Ringkasan. Suatu survey dengan prisma obyektip pada arah Palomar-Groningen Variable-Stars Field no. 3 telah diadakan guna menentukan distribusi ruang bintang-bintang dB dan gK. Sebuah konsentrasi bintang-bintang dB ditemukan pada jarak antara 150 sampai 250 pc. Harga Ekses Warna pada arah ini didapati cukup rendah. Ekses tersebut besarnya hanya mencapai Om12 pada r = 0.5 kpc dan tidak banyak berubah pada jarak-jarak yang lebih besar.